Solitary Fibrous Tumor of the Buccal Space - Dunfee, Brian L.; Sakai, Osamu; Spiegel, Jeffrey H.; Pistey, Robert (American Journal of Neuroradiology, 2005)
Summary: Solitary fibrous tumors are submesothelial mesenchymal fibroblastic tumors that typically occur in relation to parietal or visceral pleura. However, the tumor also occurs in extrapleural sites, including the peritoneum, mediastinum, orbit, and oral cavity. With the advent of immunohistochemical testing, certain tumors may be more readily identifiable; however, the diagnosis often must be reached by histomorphology and imaging studies alone. We describe a case of a solitary fibrous tumor of the buccal space, including clinical presentation, imaging characteristics, gross pathology, and histopathologic description.